Polymer solid electrolyte and solid sodium battery based on polymer solid electrolyte

By using polymer solid electrolytes prepared with polymer polymers, sodium salts and antimony-based additives, the problems of low ionic conductivity and poor interface compatibility of the electrolyte are solved, and a solid sodium metal battery with high specific energy, high safety and long life are achieved.

CN119601766AActive Publication Date: 2025-03-11UNIV OF SCI & TECH OF CHINA
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411788564.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The room temperature ion conductance of the electrolyte in polymer solid sodium metal batteries is not high, and its interface compatibility with the sodium metal negative electrode is poor, resulting in an increase in the interface impedance of the battery and limited cycle life.

Method used

Polymer solid electrolytes are prepared by polymer polymers, sodium salts and antimony-based additives. The dissociation of sodium salts is promoted through antimony-based additives and a highly stable interface layer is generated in situ at the interface, thereby inhibiting side reactions and dendrites' growth.

Benefits of technology

It significantly improves the ionic conductivity of polymer solid electrolyte and its interface compatibility with sodium metal negative electrode, extends the cyclic stability of solid sodium metal batteries and improves the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005174731200000011
    Figure HDA0005174731200000011
  • Figure HDA0005174731200000012
    Figure HDA0005174731200000012
  • Figure HDA0005174731200000013
    Figure HDA0005174731200000013
Patent Text Reader

Abstract

The invention provides a polymer solid electrolyte and a solid sodium battery based on the polymer solid electrolyte. The electrolyte is prepared from sodium salt, an antimony-based additive and a high-molecular polymer. The polymer solid electrolyte provided by the invention has relatively high ionic conductivity, has relatively strong interface compatibility with sodium metal, can effectively inhibit interface side reaction and sodium dendrite growth, is simple in preparation process, and is expected to be applied to industrial production; the polymer solid electrolyte disclosed by the invention is applied to a sodium metal symmetric battery and a sodium vanadium phosphate sodium (Na3V2 (PO4) 3) total battery, and the battery shows low polarization voltage, stable cycle performance and relatively high specific capacity and has a very good practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a preparation method and application of a polymer solid electrolyte for sodium ion batteries. Background Art

[0002] Compared with the currently widely used lithium-ion batteries, sodium-ion batteries are expected to be used in large-scale energy storage in the future because of their rich sodium resources, wide distribution, and low cost. Solid-state sodium batteries have outstanding advantages over liquid sodium batteries in terms of specific energy and safety. Among them, the sodium metal negative electrode has a high mass specific capacity (1166mAhg -1 ), low redox potential (-2.74V vs SHE), etc., so using metallic sodium as the negative electrode can further improve the energy density of solid-state sodium batteries.

[0003] Solid electrolytes are key components in solid-state batteries. Compared with inorganic solid electrolytes, polymer solid electrolytes have the advantages of good interface contact, good flexibility and easy processing. In addition, polymer solid electrolytes have many advantages such as good film-forming properties, good cost-effectiveness and good sodium salt solubility, and have great development potential.

[0004] However, polymer solid electrolytes are currently facing two problems. One is that the room temperature ionic conductivity of the electrolyte is not high, and the other is the poor compatibility of the electrolyte and the sodium metal negative electrode. This is mainly because the reduction activity of metallic sodium is high. When the polymer solid electrolyte is in direct contact with metallic sodium, interfacial side reactions are very likely to occur. The passivation layer produced at the interface by the side reaction will hinder the transmission of sodium ions, causing the battery interface impedance to increase and the battery polarization voltage to increase. In addition, due to the presence of the passivation layer, the concentration polarization on the electrode surface increases, inducing the growth of sodium dendrites, and may even pierce the polymer solid electrolyte membrane, ultimately leading to battery failure.

[0005] In order to solve these problems, researchers have adopted two main methods: one is to increase the operating temperature of the battery; the other is to introduce additives (such as oxide solid electrolytes or sulfide solid electrolytes) into the electrolyte to prepare organic-inorganic composite electrolytes. At present, these methods can improve the ionic conductivity of polymer solid electrolytes to a certain extent, but they have limited effect on enhancing the interface compatibility between polymer solid electrolytes and metallic sodium, and the cycle life of the modified polymer solid sodium battery is limited, which is difficult to meet practical applications. Therefore, it is urgent to provide a key technology for preparing solid sodium ion electrolytes, which can not only improve the ionic conductivity of polymer solid electrolytes, but also significantly enhance the interface compatibility between polymer solid electrolytes and metallic sodium, so as to achieve high specific energy, high safety and long life solid sodium metal batteries. Summary of the invention

[0006] In view of the problems of low ionic conductivity of polymer solid electrolytes and poor interface compatibility between electrolytes and metallic sodium in polymer solid sodium metal batteries, the present invention provides a method for preparing a polymer solid electrolyte with high interface compatibility. The polymer solid electrolyte provided by the present invention has high ionic conductivity, good mechanical strength and excellent interface compatibility, can significantly inhibit side reactions and dendrite growth, and realize a long-life solid sodium metal battery. The preparation method used in the present invention is simple, the cost of raw materials is low, and it is expected to be applied to large-scale production.

[0007] In order to achieve the purpose, the present invention adopts the following technical scheme:

[0008] The present invention first provides a polymer solid electrolyte for a solid sodium battery, which is prepared from a high molecular polymer, a sodium salt and an antimony-based additive. The preparation method thereof comprises the following steps:

[0009] Mixing a high molecular weight polymer and an organic solvent to obtain a polymer precursor solution;

[0010] Mixing the sodium salt, the antimony-based additive and the polymer precursor solution to obtain a polymer solid electrolyte precursor slurry;

[0011] The polymer solid electrolyte precursor slurry is coated on a mold and dried to obtain a polymer solid electrolyte membrane.

[0012] Preferably, the mass fraction of the high molecular weight polymer in the polymer precursor solution is 5 to 20 wt %, and the high molecular weight polymer is selected from one or more of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride, acrylic acid multipolymer and polyvinylidene fluoride-hexafluoropropylene;

[0013] Preferably, the mass ratio of the sodium salt to the high molecular polymer is (0.1-2):1, and the sodium salt is selected from one or more of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethylsulfonylimide, sodium tetrafluoroborate and sodium difluorooxalatoborate.

[0014] Preferably, the mass ratio of the antimony-based additive to the high molecular polymer is (0.01-0.2):1.

[0015] Preferably, the components of the antimony-based additive include Sb element and an element that can form a compound that conducts sodium ions with sodium metal (such as: O, S, Se, Te or P), and is further preferably one selected from antimony oxide, antimony sulfide, antimony selenide, antimony telluride, antimony oxysulfide, antimony sulfide selenide, antimony selenide telluride and antimony phosphide.

[0016] Preferably, the thickness of the polymer solid electrolyte is 5 to 500 μm.

[0017] The present invention also provides a solid-state sodium battery, comprising a positive electrode, a negative electrode and the above-mentioned solid electrolyte prepared from sodium salt, antimony-based additives and high molecular polymer.

[0018] Preferably, the material of the positive electrode is selected from one or more of sodium vanadium phosphate, sodium iron pyrophosphate, Prussian blue analogues and layered oxide positive electrodes, and the negative electrode is selected from one or more of sodium metal negative electrode, sodium-tin alloy negative electrode, sodium-bismuth alloy negative electrode, sodium-antimony alloy negative electrode and hard carbon negative electrode.

[0019] The beneficial effects of the present invention are embodied in:

[0020] The present invention provides a polymer solid electrolyte, which is prepared from a high molecular polymer, a sodium salt and an antimony-based additive. The antimony-based additive has a strong adsorption effect on the anions in the sodium salt, which can effectively promote the dissociation of the sodium salt, thereby improving the ionic conductivity of the electrolyte; further, the antimony-based additive can react with the sodium negative electrode to generate a highly stable interface layer in situ at the electrolyte / negative electrode interface, inhibiting the side reaction of the polymer solid electrolyte and the sodium negative electrode; in addition, the sodium antimony alloy contained in the interface layer has a strong sodium affinity, which is conducive to inducing uniform nucleation and deposition of sodium ions. Therefore, the sodium metal full battery assembled from the polymer solid electrolyte of the present invention has excellent long-cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a scanning electron microscope photograph of the polymer solid electrolyte membrane modified by the antimony sulfide additive in Example 1 of the present invention;

[0022] Figure 2 is a scanning electron microscope photograph of the unmodified polymer solid electrolyte membrane in Example 1 of the present invention;

[0023] Figure 3 This is a cycle performance diagram of a sodium||sodium symmetric battery assembled with an unmodified electrolyte at 60° C. in Example 2 of the present invention;

[0024] Figure 4 This is a cycle performance diagram of a sodium||sodium symmetric battery assembled with an antimony oxide additive modified electrolyte in Example 2 of the present invention at 60°C;

[0025] Figure 5 This is a cycle performance diagram of a sodium||sodium symmetric battery assembled with an antimony selenide additive modified electrolyte at 60° C. in Example 3 of the present invention;

[0026] Figure 6 This is a comparison diagram of the AC impedance of a sodium||sodium symmetric battery assembled with an electrolyte modified by an antimony selenide additive and a sodium||sodium symmetric battery assembled with an unmodified electrolyte at 60° C. in Example 3 of the present invention;

[0027] Figure 7 This is a cycle performance diagram of a sodium||sodium symmetric battery assembled with an antimony telluride additive-modified electrolyte in Example 4 of the present invention at 60°C;

[0028] Figure 8 This is the cycle performance diagram of the Na|Sb2Se3@PEO|Na3V2(PO4)3 solid-state sodium battery at 60°C in Example 5 of the present invention. DETAILED DESCRIPTION

[0029] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0030] In view of the problems of low electrolyte ion conductivity and serious side reactions at the interface between the electrolyte and the sodium metal negative electrode in the prior art polymer solid-state sodium metal batteries, the present invention provides a polymer solid-state electrolyte. The polymer solid-state electrolyte provided by the present invention promotes the dissociation of sodium salts due to the introduction of antimony-based additives, thereby improving the ionic conductivity of the electrolyte; in particular, the interface layer generated in situ at the interface between the additives and the sodium metal can significantly inhibit side reactions and dendrite growth, and obtain a long-life solid-state sodium metal battery. Specifically, an embodiment of the present invention discloses a polymer solid-state electrolyte prepared from a high molecular weight polymer, a sodium salt and an antimony-based additive.

[0031] In the polymer solid electrolyte provided by the present invention, the antimony-based additive is selected from one of antimony oxide, antimony sulfide, antimony selenide, antimony telluride, antimony oxysulfide, antimony sulfide selenide, antimony selenide telluride and antimony phosphide, and the antimony-based additive has the following characteristics: it contains Sb and an element that can form a compound that conducts sodium ions with sodium metal (such as: O, S, Se, Te or P). In a specific embodiment, the antimony-based compound is selected from Sb2S3, Sb2O3, Sb2Se3 and Sb2Te3. The present invention has no special restrictions on the source of the antimony-based compound, which can be prepared according to methods well known to those skilled in the art, or can be commercially available.

[0032] The sodium salt is selected from one or more of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethylsulfonyl imide, sodium tetrafluoroborate and sodium difluorooxalatoborate.

[0033] The high molecular polymer is mainly used for film formation and sodium ion conduction, and is selected from one or more of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride, acrylic acid multi-polymer and polyvinylidene fluoride-hexafluoropropylene.

[0034] The mass ratio of the sodium salt to the high molecular polymer is (0.1-2): 1. Further preferably, the mass ratio of the sodium salt to the high molecular polymer is (0.3-1.5): 1. A moderate increase in the content of the sodium salt can enhance the ability of the electrolyte to conduct sodium ions, but due to the decrease in the high molecular polymer content, the mechanical stability of the polymer solid electrolyte will decrease, resulting in a decrease in long-cycle stability; when the sodium salt content is too low, the corresponding proportion of the high molecular polymer increases, which can improve the flexibility of the polymer solid electrolyte, but the sodium ion conduction rate decreases, and the corresponding ionic conductivity decreases.

[0035] The mass ratio of the antimony-based additive to the high molecular polymer is (0.01-0.2):1. Further preferably, the mass ratio of the antimony-based additive to the high molecular polymer is (0.02-0.15):1. If the content of the antimony-based additive is too large, it is beneficial to form a stable interface layer at the interface, but due to the decrease in the content of the high molecular polymer, the toughness of the polymer solid electrolyte will decrease; if the content of the antimony-based additive is too small, the corresponding proportion of the high molecular polymer will increase, which can improve the flexibility of the polymer solid electrolyte, but the ability to promote the dissociation of the sodium salt will decrease, making it difficult to form a stable interface layer, resulting in serious interface side reactions and deterioration of battery performance.

[0036] In the present invention, the thickness of the polymer solid electrolyte is 5 to 500 μm. Further preferably, the thickness of the polymer solid electrolyte is 20 to 100 μm. If the thickness of the polymer solid electrolyte is too thin, it is conducive to the rapid transmission of sodium ions, but the mechanical properties are deteriorated and the ability to inhibit sodium dendrites is weakened; if it is too thick, the mechanical properties are enhanced, but it is not conducive to the rapid transmission of sodium ions, resulting in concentration polarization of the battery and increased battery impedance.

[0037] Furthermore, the present invention provides a method for preparing a polymer solid electrolyte, comprising the following steps:

[0038] First, a polymer is added to an organic solvent to prepare a polymer precursor solution. In this process, the organic solvent is selected from a solvent that can dissolve the polymer, specifically N-methylpyrrolidone (NMP), acetone, acetonitrile or N, N-dimethylformamide (DMF), more preferably acetonitrile. The mass fraction of the polymer in the polymer precursor solution is 5 to 20wt%, more preferably 8 to 15wt%.

[0039] Then, the sodium salt, antimony-based additive and polymer precursor liquid are fully stirred and mixed to obtain a polymer solid electrolyte precursor slurry; the polymer solid electrolyte precursor slurry is coated on the mold, and the polymer solid electrolyte is obtained after drying. The coating method can be carried out in a manner familiar to those skilled in the art, and there is no special restriction on this in the present invention. For example, scraping, dripping or spin coating can be used. The drying specifically adopts vacuum drying or natural evaporation drying. Specifically, the drying method is natural evaporation drying first and then vacuum drying. The drying temperature is 20-60°C, the natural evaporation drying time is 5-24h, and the vacuum drying time is 4-24h. It is further preferred that the natural evaporation drying time is 12-24h, and the vacuum drying time is 6-12h.

[0040] Furthermore, the present invention provides a solid-state sodium metal battery, which applies the above-mentioned polymer solid electrolyte to a solid-state sodium battery; specifically, the solid-state sodium battery includes a polymer solid electrolyte, a positive electrode and a negative electrode.

[0041] In the solid-state sodium battery provided by the present invention: the material of the positive electrode is selected from one or more of sodium vanadium phosphate, sodium iron pyrophosphate, Prussian blue analogs and layered oxide positive electrodes. In an embodiment of the present invention, the material of the positive electrode is selected from sodium vanadium phosphate. The present invention has no special restrictions on the source of the sodium vanadium phosphate, which can be prepared according to methods well known to those skilled in the art, or it can be commercially available. The negative electrode is selected from one or more of a sodium metal negative electrode, a sodium-tin alloy negative electrode, a sodium-bismuth alloy negative electrode, a sodium-antimony alloy negative electrode and a hard carbon negative electrode. In an embodiment of the present invention, the material of the negative electrode is selected from a sodium metal negative electrode, and the present invention has no special restrictions on the source of the sodium metal, which can be prepared according to methods well known to those skilled in the art, or it can be commercially available.

[0042] The solid-state sodium metal full battery provided by the present invention can effectively inhibit the interfacial side reactions between the electrolyte and the sodium metal negative electrode, promote the transmission of sodium ions at the interface, induce the uniform deposition of sodium ions, reduce the internal resistance of the battery interface, and thus enhance the cycle stability of the solid-state sodium metal full battery.

[0043] In order to further understand the present invention, the polymer solid electrolyte and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0044] Example 1

[0045] Dissolve 0.2g polyethylene oxide in acetonitrile and mix and stir to obtain a polymer precursor solution with a mass fraction of 10wt%, add 85mg sodium bis(trifluoromethylsulfonyl)imide and 10mg antimony sulfide (Sb2S3) to the polymer precursor solution and mix and stir to obtain a polymer solid electrolyte precursor slurry. Apply the polymer solid electrolyte precursor slurry on the mold, evaporate and dry naturally at room temperature for more than 12 hours, and then vacuum dry at room temperature for more than 6 hours to remove the solvent. After drying, cut to obtain an antimony sulfide-modified polymer solid electrolyte membrane with a thickness of about 50μm.

[0046] For comparison, an unmodified polymer solid electrolyte membrane is also prepared in this embodiment, and its preparation process is basically the same as the above process, except that no antimony sulfide additive is added.

[0047] Figure 1 This is a scanning electron microscope photo of a polymer solid electrolyte membrane modified with antimony sulfide additive. It can be seen that there are no obvious pores on the surface of the modified electrolyte membrane and the surface is dense and uniform. Figure 2 This is a scanning electron microscope photo of a polymer solid electrolyte membrane that has not been modified with antimony sulfide. It can be seen that the surface of the unmodified polymer solid electrolyte membrane has obvious pores and is not dense. Figure 1 and Figure 2 It can be seen that the introduction of antimony sulfide additives can significantly improve the density of the electrolyte, which is beneficial to improving the density and mechanical strength of the electrolyte membrane, thereby inhibiting dendrite growth.

[0048] Example 2

[0049] Dissolve 0.4g polyethylene oxide in acetonitrile and mix and stir to obtain a polymer precursor solution with a mass fraction of 10wt%, add 0.17g sodium bis(trifluoromethylsulfonyl)imide and 20mg antimony oxide (Sb2O3) to the polymer precursor solution and mix and stir to obtain a polymer solid electrolyte precursor slurry. Apply the polymer solid electrolyte precursor slurry on the mold, evaporate and dry naturally at room temperature for more than 12 hours, and then vacuum dry at room temperature for more than 6 hours to further remove the solvent. After drying, cut to obtain an antimony oxide-modified polymer solid electrolyte membrane with a thickness of about 50μm.

[0050] For comparison, an unmodified polymer solid electrolyte membrane was also prepared in this embodiment, and its preparation process was basically the same as the above process, except that no antimony oxide additive was added.

[0051] The polymer solid electrolyte membrane prepared as above is used as electrolyte and the sodium metal foil is used as electrode to assemble a sodium|sodium button-type symmetrical battery. Figure 3 The sodium||sodium symmetric battery assembled with unmodified electrolyte at 0.1 mA cm -2Time-voltage curve under current density. It can be seen from the figure that the polarization voltage of the sodium||sodium symmetric battery is about 200mV, and the battery short circuit occurs in less than 10h of cycle. Figure 4 The sodium||sodium symmetric battery (Sb2O3@PEO) assembled with antimony oxide additive-modified electrolyte has a high conductivity at 0.1 mA cm -2 Time-voltage curve under current density. It can be seen from the figure that the polarization voltage of the sodium||sodium symmetric battery assembled with antimony oxide additive-modified electrolyte is about 20mV after 100h of cycling, which is lower than that of the symmetric battery assembled with unmodified electrolyte. This indicates that the introduction of antimony oxide additive can inhibit interfacial side reactions and significantly extend the cycle life of the battery.

[0052] Example 3

[0053] Dissolve 0.4g polyethylene oxide in acetonitrile and mix and stir to obtain a polymer precursor solution with a mass fraction of 10wt%, add 0.17g sodium bis(trifluoromethylsulfonyl)imide and 20mg antimony selenide (Sb2Se3) to the polymer precursor solution and mix and stir to obtain a polymer solid electrolyte precursor slurry. Apply the polymer solid electrolyte precursor slurry on the mold, evaporate and dry naturally at room temperature for more than 12 hours, and then vacuum dry at room temperature for more than 6 hours to remove the solvent. After drying, cut to obtain a polymer solid electrolyte membrane modified with antimony selenide additive, with a thickness of about 50μm.

[0054] The polymer solid electrolyte membrane prepared as above is used as electrolyte and the sodium metal foil is used as electrode to assemble a sodium|sodium button-type symmetrical battery. Figure 5 The sodium||sodium symmetric battery (Sb2Se3@PEO) assembled with antimony selenide additive-modified polymer solid electrolyte has a high conductivity at 0.1 mA cm -2 The time-voltage curve under current density is given by Figure 5 It can be seen that the polarization voltage of the sodium||sodium symmetric battery assembled with polymer solid electrolyte modified by antimony selenide additive is relatively stable as the cycle progresses. When the cycle reaches 500h, the polarization voltage is about 20mV. Figure 6 This is a comparison of the AC impedance spectra of polymer solid electrolytes containing antimony selenide additives and those without antimony selenide additives. Figure 6 It can be seen that the addition of antimony selenide can significantly reduce the impedance of the battery, which indicates that the introduction of antimony selenide helps to inhibit the interfacial side reactions between the electrolyte and sodium metal and enhance the cycle stability of the battery.

[0055] Example 4

[0056] Dissolve 0.4g polyethylene oxide in acetonitrile and mix and stir to obtain a polymer precursor solution with a mass fraction of 10wt%, add 0.17g sodium bis(trifluoromethylsulfonyl)imide and 20mg antimony telluride (Sb2Te3) to the polymer precursor solution and mix and stir to obtain a polymer solid electrolyte precursor slurry. Apply the polymer solid electrolyte precursor slurry on the mold, evaporate and dry naturally at room temperature for more than 12 hours, and then vacuum dry at room temperature for more than 6 hours to remove the solvent. After drying, cut to obtain a polymer solid electrolyte membrane modified with antimony telluride additive, with a thickness of about 50μm.

[0057] The polymer solid electrolyte membrane prepared as above is used as electrolyte and the sodium metal foil is used as electrode to assemble a sodium|sodium button-type symmetrical battery. Figure 7 The sodium||sodium symmetric battery (Sb2Te3@PEO) assembled with antimony telluride additive-modified polymer solid electrolyte has a high conductivity at 0.1 mA cm -2 The time-voltage curve under current density is given by Figure 7 It can be seen that as the cycle progresses, the polarization voltage of the sodium||sodium symmetric battery is smaller. When the cycle reaches 200h, the polarization voltage is about 20mV.

[0058] Example 5

[0059] 0.7g sodium vanadium phosphate (Na3V2(PO4)3), 0.1g conductive carbon black and 0.2g PVDF binder (containing a small amount of sodium perchlorate) are mixed, ground and stirred evenly, coated on carbon-coated aluminum foil, dried in a vacuum oven at 60°C, and cut to obtain a positive electrode sheet after drying. 0.4g polyethylene oxide is dissolved in acetonitrile and mixed and stirred evenly to obtain a polymer precursor solution with a mass fraction of 10wt%, 0.17g sodium bistrifluoromethylsulfonyl imide and 20mg antimony selenide (Sb2Se3) are added to the polymer precursor solution and mixed and stirred evenly to obtain a polymer solid electrolyte precursor slurry. The polymer solid electrolyte precursor slurry is coated on a mold, dried by natural evaporation at room temperature for more than 12 hours, and then vacuum dried at room temperature for 6 hours to remove the solvent. After drying, the antimony selenide additive-modified polymer solid electrolyte membrane is cut to obtain a thickness of about 50μm.

[0060] Using sodium metal foil as the negative electrode, a Na|Sb2Se3@PEO|Na3V2(PO4)3 solid-state sodium battery was assembled. Figure 8 This is the cycle performance curve of Na|Sb2Se3@PEO|Na3V2(PO4)3 solid-state sodium battery. The first 5 cycles are at 10mAg -1 The activation was carried out at a low current density of 100 mA. -1 The cycle is carried out at a current density of Figure 8 It can be seen that at 100mAg -1At a current density of 1.3 200 mAh g / cm2, the specific capacity of Na|Sb2Se3@PEO|Na3V2(PO4)3 solid-state sodium battery is about 100 mAh g / cm2 after 50 cycles. -1 There is no obvious capacity decay phenomenon, indicating that the modified electrolyte and sodium vanadium phosphate positive electrode have good compatibility.

[0061] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A polymer solid electrolyte, characterized in that: It is prepared from sodium salt, antimony-based additives and high molecular polymers.

2. The polymer solid electrolyte according to claim 1, characterized in that The antimony-based additive comprises Sb element and an element capable of forming a compound that conducts sodium ions with sodium metal.

3. The polymer solid electrolyte according to claim 2, characterized in that: The element capable of forming a sodium ion-conducting compound with sodium metal is one or more of O, S, Se, Te and P.

4. The polymer solid electrolyte according to claim 1 or 2, characterized in that: The sodium salt is selected from one or more of sodium bis(trifluoromethylsulfonyl)imide, sodium bis(fluorosulfonyl)imide, sodium hexafluorophosphate, sodium perchlorate, sodium trifluoromethylsulfonyl imide, sodium tetrafluoroborate and sodium difluorooxalatoborate; the antimony-based additive is selected from one or more of antimony oxide, antimony sulfide, antimony selenide, antimony telluride, antimony oxysulfide, antimony sulfoselenide, antimony selenide telluride and antimony phosphide; the high molecular polymer is selected from one or more of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride, acrylic copolymer and polyvinylidene fluoride-hexafluoropropylene.

5. The polymer solid electrolyte according to claim 1 or 2, characterized in that: The mass ratio of the sodium salt to the high molecular polymer is 0.1-2:1; the mass ratio of the antimony-based additive to the high molecular polymer is 0.01-0.2:

1.

6. The polymer solid electrolyte according to claim 1 or 2, characterized in that: The thickness of the polymer solid electrolyte is 5 to 500 μm.

7. A method for preparing the polymer solid electrolyte according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing a high molecular weight polymer and an organic solvent to obtain a polymer precursor solution; Mixing the sodium salt, the antimony-based additive and the polymer precursor solution to obtain a polymer solid electrolyte precursor slurry; The polymer solid electrolyte precursor slurry is coated on a mold and dried to obtain a polymer solid electrolyte.

8. The preparation method according to claim 7, characterized in that: The mass fraction of the high molecular weight polymer in the polymer precursor solution is 5 to 20 wt %.

9. A solid-state sodium battery, comprising a positive electrode, a negative electrode and a solid electrolyte, characterized in that: The solid electrolyte is the polymer solid electrolyte described in any one of claims 1 to 6 or the polymer solid electrolyte prepared by the preparation method described in claim 7 or 8.

10. The solid-state sodium battery according to claim 9, characterized in that: The material of the positive electrode is selected from one or more of sodium vanadium phosphate, sodium iron pyrophosphate, Prussian blue analogs and layered oxide positive electrodes, and the negative electrode is selected from one or more of sodium metal negative electrodes, sodium-tin alloy negative electrodes, sodium-bismuth alloy negative electrodes, sodium-antimony alloy negative electrodes and hard carbon negative electrodes.

Citation Information

Patent Citations

  • NASICON-structured sodium ion solid electrolyte, preparation method thereof, and solid sodium ion battery

    CN108695552A

  • All-solid sodium secondary battery electrolyte and preparation method and application thereof

    CN108695553A

  • Sodium ion composite polymer solid electrolyte and preparation method thereof

    CN114725506A

  • Micron-sized antimony compound as well as preparation method and application thereof

    CN116742168A

  • High-voltage-resistant electrolyte and application thereof in high-power graphite-antimony sodium-based dual-ion battery

    CN118367217A